Understanding Farmers’ perception of the conversion of agricultural land to non-agricultural land in Bangkalan Regency - Lubis, Zulfikar Nursyady; Priyanto, Moh. Wahyudi; Rum, Mokh. (Agriculture Socio-Economic Department, Faculty of Agriculture, Brawijaya University, 2025)
Conversion of agricultural land to non-agricultural land is an increasing phenomenon, especially in the outskirts of Bangkalan Regency which is experiencing growth in the residential sector. This study aims to analyze farmers' perceptions of conversion of agricultural land using a descriptive statistical analysis approach. Data were obtained through direct interviews with 50 farmer respondents using the accidental sampling method. The results of the study indicate that the main factors that encourage farmers to convert land are low agricultural yields and high land prices, followed by water scarcity and minimal incentives from the government. Meanwhile, the distance to educational and health facilities is considered to have the lowest influence on land conversion decisions. Therefore, policies are needed that support agricultural sustainability through land protection and improving farmer welfare.